Book Reviews. Issue 2 (1st September 2017) - Lennox, Patricia; Taylor, Madeline
Designers' Shakespeare, John Russell Brown and Stephen Di Benedetto (2016)New York and Oxon: Routledge, 200 pp., ISBN: 9780415618007, h/bk, £95, p/bk, £32.99The Art and Practice of Costume Design, Melissa L. Merz (ed.) (2017)New York and London: Routledge, 310 pp., ISBN: 9781138828414, p/bk